Propuestas para Fortalecer la Cultura Emprendedora en los Municipios de Puebla y Tlaxcala (2019)
The present research work Its main purpose is to make some proposals to strengthen the entrepreneurial culture in the municipalities of Puebla and Tlaxcala in Mexico, considering the results of the application of an instrument to entrepreneurs, which for this particular case was a survey with nine statements, seeking to identify entrepreneurs' perception of whether the analyzed aspects are met, finding that in both municipalities there are several similarities that contribute in an important way in the entrepreneurial process, but it is necessary to intensify some actions that Foster an Entrepreneurial Mindset and it is concluded that the proposals made could improve the existing Entrepreneurial culture, but it requires the participation of all the actors involved in the entrepreneurial phenomenon.